The Community System Based on Kolo Bian Myth in East Nusa Tenggara - Moses Glorino Rumambo Pandin; Mohd Roslan Mohd Nor (Universitas Airlangga, 2022)
The main objective of this study is to analyze the Weoe community system in the Kolo Bian myth of East Nusa Tenggara. The method used was a literature review through structural analysis and reflection on the story of the Kolo Bian myth. The findings showed that the Weoe people's genealogical development process is reflected in the power system that has developed in the trade and marriage patterns. In particular, the marriage pattern is a means of perpetuating the power system. The participation of local authorities, who are integrated into Â groups and given new customs, plays a role in supporting the continuation of power. Faith-based organizations in the community support this pattern of power systems both politically and spiritually. The power system is not enforced by the rulers on the existing society; instead, the people welcome the presence of rulers who position themselves lower than the real rulers coming from expulsion on other lands or areas. The power system in Weoe society is preserved in this habitus. The power system is then formed in the concatenation of the marriage system.